Pengaruh Penghargaan dan Motivasi Terhadap Kinerja Karyawan (Studi Pada Divisi Penjualan PT. United Motors Center Suzuki Ahmad Yani, Surabaya) - Prabu, Aldila Saga; Wijayanti, Dewie Tri (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2016)
Human Resources (HR) is a major asset that greatly affect the company's progress. Human  resourcesas a driver of creativity and innovation in a company which will enhance the company'sreputation and profit. In order to achieve the company's goals is necessary to reward andmotivation for each individual to be able to work better. This study aims to describe, test, andanalyze whether the effect of rewards and motivation on employee performance in the salesdivision of PT. United Motors Center Suzuki Ahmad Yani, Surabaya. The sampling techniqueusing sampling techniques saturated. The research population is all employees of the salesdivision of PT. United Motors Center Suzuki Ahmad Yani, Surabaya numbering 70 people.Theanalytical method used is multiple linear regression with SPSS version 15.0. The results showthat there is a positive and significant effect of the variable reward and motivation on employeeperformance sales division of PT. United Motors Center Suzuki Ahmad Yani, Surabaya.